Comprehensible instructions from assistive robots for older adults with or without cognitive impairment. Issue 5 (3rd September 2022) - Nishiura, Yuko; Nihei, Misato; Takaeda, Kana; Inoue, Takenobu
ABSTRACT: The purpose of this study was to reveal comprehensible instructions from an assistive robot for older adults, across cognitive levels and characteristics. Participants included 19 older adults with or without cognitive impairment. We administered cognitive tests assessing all major domains (e.g., memory and attention). Participants were required to listen to robot instructions carefully, and perform three activities of daily living (e.g., taking medicine) with three different types of instructions. In instruction pattern 1 (IP1), the robot informed seniors of the task in one sentence, while in instruction patterns 2 and 3 (IP2 and IP3), the steps of each activity were split into two and three sentences, respectively. Participants with lower cognitive level showed lower task performance with IP1, whereas almost all participants completed tasks with IP2 and IP3. Cognitive domains such as working memory significantly affected task performances. Participants with lower attention made mistakes in taking their medicine. The results imply that step-by-step instructions should be used for older people with lower levels of cognitive function, especially working memory, and repeated instructions may be required for lower attention. Types of instruction should be selected depending on cognitive characteristics.